Cross-link augmentation enhances CFR-PEEK short fixation in lumbar metastasis stabilization - Borrelli, Simone; Putame, Giovanni; Audenino, Alberto L.; Bignardi, Cristina; Ferro, Andrea; Marone, Stefano; Terzini, Mara (Frontiers in Bioengineering and Biotechnology, 2023)
Spinal stability plays a crucial role in the success of the surgical treatment of lumbar vertebral metastasis, and in the current practice, less invasive approaches such as short construct have been considering. Concurrently, carbon fiber reinforced (CFR) poly-ether-ether-ketone (PEEK) fixation devices are expanding in oncologic spinal surgery thanks to its radiotransparency and valid mechanical properties. This study attempts to provide an exhaustive biomechanical comparison of different CFR-PEEK surgical stabilisations through a high-reproducible experimental setup. A Sawbones biomimetic phantom (T12-S1) was tested in flexion, extension, lateral bending, and axial rotation. An hemisome lesion on L3 vertebral body was mimicked and different pedicle screw posterior fixations were realised recurring to CarboFix Orthopedics Ltd instruments: a long construct involving two spinal levels above and below the lesion, and a short construct involving only the adjacent levels of L3, with and without the addition of a transverse rod-rod cross-link; to provide additional insights on its long-term applicability, the event of a pedicle screw loosening was also accounted. Short constructs reduced the overloading onset caused by the long stabilisation. Particularly, they revealed a more physiologic motion contribution profile of vertebral joints and a more conservative long-chain stiffness with respect to the prevalent long one. The use of cross-link enhanced the short stabilisation by making it significantly stiffer in lateral bending and axial rotation, and by limiting the mobilisation in case of pedicle screw loosening. The present study proved in vitro the biomechanical benefits of cross-link augmentation in short CFR-PEEK fixation, demonstrating to be a potential alternative to standard long fixation in the surgical management of lumbar metastasis.